The effect of background music on the taste of wine - North, Adrian (John Wiley & Sons Ltd, 2012)
Research concerning cross-modal influences on perception has neglected auditory influences on perceptions of non-auditory objects, although a small number of studies indicate that auditory stimuli can influence perceptions of the freshness of foodstuffs. Consistent with this, the results reported here indicate that independent groups’ ratings of the taste of the wine reflected the emotional connotations of the background music played while they drank it. These results indicate that the symbolic function of auditory stimuli (in this case music) may influence perception in other modalities (in this case gustation); and are discussed in terms of possible future research that might investigate those aspects of music that induce such effects in a particular manner, and how such effects might be influenced by participants’ pre-existing knowledge and expertise with regard to the target object in question.